1990
DOI: 10.3109/00365529008998554
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Unsaturated Vitamin B12-Binding Capacity and Myeloperoxidase as Indices of Severity of Acute Inflammation in Serial Colonoscopy Biopsy Specimens from Patients with Inflammatory Bowel Disease

Abstract: Measurements of tissue content of myeloperoxidase, a constituent of neutrophil azurophil granules and of unsaturated vitamin B12-binding protein from neutrophil-specific granules, have been used to assess intestinal inflammation. This paper reports results of a prospective evaluation of such measurements in serial colonoscopy biopsy specimens from patients with inflammatory bowel disease. Histologic grading of acute inflammation was based on perceived numbers of neutrophil polymorphs in sections from an immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Forty‐two intestinal biopsy samples from 11 patients with CD, 59 from 18 patients with UC, and 121 from 37 non‐IBD patients were studied (Table 1). The diagnosis of CD and UC was made on the basis of established clinical, radiological, endoscopic and pathological criteria 5,21 . None of the patients were on antibiotic treatment at the time of colonoscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Forty‐two intestinal biopsy samples from 11 patients with CD, 59 from 18 patients with UC, and 121 from 37 non‐IBD patients were studied (Table 1). The diagnosis of CD and UC was made on the basis of established clinical, radiological, endoscopic and pathological criteria 5,21 . None of the patients were on antibiotic treatment at the time of colonoscopy.…”
Section: Methodsmentioning
confidence: 99%
“…It is found in the secondary granules of mature neutrophils. Its role in psoriasis has not been emphasized, although levels of TCN1 protein are correlated with the severity of intestinal inflammation in Crohn's disease and RA (51)(52)(53). Elevation of TCN1 has been thought to be responsible for the elevation of vitamin B12 in a number of chronic myeloproliferative disorders (54).…”
Section: Transcobalamin 1 Up-regulationmentioning
confidence: 99%
“…MPO is an important peroxidase that exists mainly in neutrophils: its level reflects the degree of neutrophil infiltration and acts as an indirect measure of the presence of tissue inflammation [15]. Several studies demonstrated that MPO activity is related to the severity of intestinal inflammation [16,17]. Our measurements of MPO activity indicate that infiltration of inflammatory cells, especially neutrophil granulocytes, did indeed occur during the period of acute colitis induced by TNBS, since MPO levels were significantly increased in the TNBS-induced colitis group.…”
mentioning
confidence: 99%